2020
DOI: 10.1080/02692171.2020.1782854
|View full text |Cite
|
Sign up to set email alerts
|

Does the financial system support economic growth in times of financialisation? Evidence for Portugal

Abstract: The purpose of this paper is the conduction of a time series econometric analysis in order to examine empirically the relationship between the financial system and economic growth in Portugal from 1977 to 2016. The Portuguese financial system has experienced a strong wave of privatisations, liberalisations and deregulations since the adhesion of Portugal to the European Economic Community in 1986, which has not favoured a sustained path of strong economic growth since then. The growth of the financial system p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 60 publications
(137 reference statements)
2
40
1
Order By: Relevance
“…This is the so-called 'savings effect' (Altman, 1998). Fifth, an increase in labour income share drives 'natural selection' or 'creative destruction' in a context in which routine corporations and/or laggards are 2 Barradas (2020) explains in detail why there has been a negative relationship between the phenomenon of financialisation and economic growth in the last decades, which has been confirmed by the emergence of several empirical works that have found a reversal of the traditional hypothesis of the finance-growth nexus Valev, 2004a, 2004b;Aghion et al, 2005;Kose et al, 2006;Prasad et al, 2007;Rousseau andWachtel, 2011, Cecchetti andKharroubi, 2012;Barajas et al, 2013;Dabla-Norris and Srivisal, 2013;Beck et al, 2014;Breintenlechner et al, 2015;Alexiou et al, 2018;Ehigiamusoe and Lean, 2018;Barradas, 2020). 3 Hein (2012), , Barradas (2019) and Kohler et al (2019) describe how the phenomenon of financialisation has contributed to the fall in labour income share in the last few decades.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the so-called 'savings effect' (Altman, 1998). Fifth, an increase in labour income share drives 'natural selection' or 'creative destruction' in a context in which routine corporations and/or laggards are 2 Barradas (2020) explains in detail why there has been a negative relationship between the phenomenon of financialisation and economic growth in the last decades, which has been confirmed by the emergence of several empirical works that have found a reversal of the traditional hypothesis of the finance-growth nexus Valev, 2004a, 2004b;Aghion et al, 2005;Kose et al, 2006;Prasad et al, 2007;Rousseau andWachtel, 2011, Cecchetti andKharroubi, 2012;Barajas et al, 2013;Dabla-Norris and Srivisal, 2013;Beck et al, 2014;Breintenlechner et al, 2015;Alexiou et al, 2018;Ehigiamusoe and Lean, 2018;Barradas, 2020). 3 Hein (2012), , Barradas (2019) and Kohler et al (2019) describe how the phenomenon of financialisation has contributed to the fall in labour income share in the last few decades.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to post-Keynesian literature, and as emphasised by Orhangazi (2008), Hein and van Treeck (2010) and Hein (2012), the phenomenon of financialisation has impaired real investment realised by corporations for two different reasons. The phenomenon of financialisation has led to 4 Lagoa and Barradas (2020) clarified to what extent the phenomenon of financialisation has exerted a positive impact on personal income inequality in the last decades, which has been corroborated by the emergence of several empirical works that have found a positive relationship between the phenomenon of financialisation and personal income inequality (Greenwood and Jovanovic, 1990;Banerjee and Newmann, 1993;Galor and Zeira, 1993;Baldacci et al, 2002;Roine et al, 2009;Atkinson and Morelli, 2011;Gimet and Lagoarde-Segot, 2011;Assa, 2012;Fournier and Koske, 2012;Jauch and Watzka, 2012;Jaumotte et al, 2013;Karanassou and Sala, 2013;Denk and Cournede, 2015;Furceri and Loungani, 2015;Jaumotte and Buitron, 2015;Han and Sturm, 2017;Baiardi and Morana, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These authors call this the "decoupling hypothesis" between the financial system and the real economy. In the same vein, Cecchetti and Kharroubi (2012), Barajas, Chami, and Yousefi (2013), Dabla-Norris and Srivisal (2013), Beck, Degryse, and Kneer (2014), Barradas (2020) and Pariboni, Meloni, and Tridico (2020) conclude that there has been a nonlinear relationship between finance and economic growth as a concave quadratic function, in a context where finance has an inverted U-shaped effect on economic growth. This means that from a certain threshold a further enlargement of the financial system can even reduce economic growth.…”
Section: Literature Review On the Finance-growth Nexus: Theoretical A...mentioning
confidence: 95%
“…69, Issue 4, pp. 527-554 relationship between finance and economic growth or even a negative relationship between them (Felix Rioja and Neven Valev 2004a, b;Philippe Aghion, Peter Howitt, and David Mayer-Foulkes 2005; M. Ayhan Kose et al 2006;Eswar S. Prasad, Raghuram G. Rajan, and Arvind Subramanian 2007;Rousseau and Wachtel 2011;Stephen G. Cecchetti and Enisse Kharroubi 2012;Barajas, Chami, and Yousefi 2013;Dabla-Norris and Srivisal 2013;Beck, Degryse, and Kneer 2014;Max Breitenlechner, Martin Gächter, and Friedrich Sindermann 2015;Ehigiamusoe and Lean 2017;Constantinos Alexiou, Sofoklis Vogiazas, and Joseph Nellis 2018;Barradas 2020;Pariboni, Meloni, and Tridico 2020). Lukas Menkhoff and Norbert Tolksdorf (2001) stress that there has been a "disruptive relationship" between finance and economic growth in the last ten or twenty years, because the financial sphere started to follow its own logic and the real economy began to adapt to the consequences of this.…”
Section: Literature Review On the Finance-growth Nexus: Theoretical A...mentioning
confidence: 99%
“…Sawyers showed that as financialization increases in an economy economic performance is negatively affected. Barradas (2020), analyzed the relationship between financial mobility and economic growth in Portugal from 1977 to 2016. The findings suggest a negative relationship between financial mobility and economic growth.…”
Section: Foreign Direct Investments (Fdi) and Economic Growthmentioning
confidence: 99%